Modern weapons and military equipment for issue 3-2018 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2018)
China's Type 99 Tank: Could It Beat an M1 Abrams or Russia's T-90?North Korean military parade, North Korea parades two classes of ICBM for the first time, North Korea unveils new mobile short-range ballistic missile system.Saab touts biz-jet-based GlobalEye and Swordfish platforms.